Ca(2+) Sparks Act as Potent Regulators of Excitation-Contraction Coupling in Airway Smooth Muscle - ZhuGe, Ronghua (American Society for Biochemistry and Molecular Biology, 2010)
Ca(2+) sparks are short lived and localized Ca(2+) transients resulting from the opening of ryanodine receptors in sarcoplasmic reticulum. These events relax certain types of smooth muscle by activating big conductance Ca(2+)-activated K(+) channels to produce spontaneous transient outward currents (STOCs) and the resultant closure of voltage-dependent Ca(2+) channels. But in many smooth muscles from a variety of organs, Ca(2+) sparks can additionally activate Ca(2+)-activated Cl(−) channels to generate spontaneous transient inward current (STICs). To date, the physiological roles of Ca(2+) sparks in this latter group of smooth muscle remain elusive. Here, we show that in airway smooth muscle, Ca(2+) sparks under physiological conditions, activating STOCs and STICs, induce biphasic membrane potential transients (BiMPTs), leading to membrane potential oscillations. Paradoxically, BiMPTs stabilize the membrane potential by clamping it within a negative range and prevent the generation of action potentials. Moreover, blocking either Ca(2+) sparks or hyperpolarization components of BiMPTs activates voltage-dependent Ca(2+) channels, resulting in an increase in global [Ca(2+)](i) and cell contraction. Therefore, Ca(2+) sparks in smooth muscle presenting both STICs and STOCs act as a stabilizer of membrane potential, and altering the balance can profoundly alter the status of excitability and contractility. These results reveal a novel mechanism underlying the control of excitability and contractility in smooth muscle.